10=3g-1

Simple and best practice solution for 10=3g-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=3g-1 equation:


Simplifying
10 = 3g + -1

Reorder the terms:
10 = -1 + 3g

Solving
10 = -1 + 3g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-3g' to each side of the equation.
10 + -3g = -1 + 3g + -3g

Combine like terms: 3g + -3g = 0
10 + -3g = -1 + 0
10 + -3g = -1

Add '-10' to each side of the equation.
10 + -10 + -3g = -1 + -10

Combine like terms: 10 + -10 = 0
0 + -3g = -1 + -10
-3g = -1 + -10

Combine like terms: -1 + -10 = -11
-3g = -11

Divide each side by '-3'.
g = 3.666666667

Simplifying
g = 3.666666667

See similar equations:

| 6x-2y=90 | | 6-2y=90 | | 2(n-4)+n-10= | | 3x^3+x^2-4x^3-5x= | | 14x+2((90+6x)/2)=110 | | x^4-x^2-2x+1=0 | | 6(2x+1)=x | | 3x^2+x^2-4x^3-5x= | | -3(-2)+y=3 | | -9(2x-6y)= | | 3x+2(3x+3)=-12 | | 5x-(10y)=65 | | x^2+-6x+6=0 | | 5(x+x)-3(3x+2)=-5(x-6)+2 | | 2[3-3(x+1)]+1=2(-25-x)+2x+25 | | 11x+10x+x= | | x^4+20x^3-10x^2+10x-20=0 | | 1/13b=-2.37 | | -7.6q+1.3=-11.5-1.2q | | X/13=4 | | 8+4*4= | | 9x^2-2x-6x^2-2x= | | 3x+(2x+1)=11 | | 135/39 | | 2H+D=3D^2 | | 3x-2((15-x)/2)=5 | | 11x-9-5=10x-3 | | 3x^2=6x+24 | | y=-7/4x | | 4(w-9)=7w+19 | | 4x=5x+10 | | (2x^2+13x+19)/(x+5) |

Equations solver categories